Educational Value Of Tauhid In Acehnese Poem “RATÉB DÔDA IDI” Study Of Local Wisdom In Aceh Besar Community - Yusri Yusuf; M. Hasbi Amiruddin; Syabuddin Gade (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2020)
Ratéb Dôda Idi is one of the local wisdoms in Aceh Besar community in educating early childhood. They put their children to sleep in a swing and chant poem that contains the value of monotheism. Previous research explains, Ratéb Dôda Idi as childcare media, character building, and socio-cultural functions. At present, there are still parents who use Ratéb Dôda Idi as a medium for children's education, but some do not use it. Poem of Ratéb Dôda Idi is often contested, and the Aceh’s Tradition Council has done the training. This study aims to find answers to the poem of Ratéb Dôda Idi used as a medium of transferring monotheism value and how relevant it is to the future development of Islam in Aceh Besar. This research uses a qualitative approach and “social situation”, descriptive method, text analysis, purposive informants, interview technique snowball, and triangulation. The results of the study answer that: First, Ratéb Dôda Idi used as a medium of transferring monotheism value to children, with the reasons: (1) poem has become a tradition in society; (2) poem is entertainment for children and parents; (3) poem is appropriate to the child character; (4) rewarding those who read it. Second: Ratéb Dôda Idi is relevant to Islamic education, with reason: poem of Ratéb Dôda Idi and Islamic religious education both aim to form a pious man and virtuous character; (2) poem of ratéb dôda idi and Islamic education both contain monotheism, worship, and morals; (3) it is known that the role of parents in poem ratéb dôda idi is appropriate to Islamic teachings, namely the most responsible ones to children’s education is parents. Ratéb Dôda Idi needs to be preserved and adapted to the times. Ratéb Dôda Idi is an investment for children's education from now on in Aceh Besar community.